Integrating a youth participation model in a youth mental health service: Challenges and lessons learned. Issue 3 (2nd July 2016) - Coates, Dominiek; Howe, Deborah
ABSTRACT: Youth participation in mental health settings is fundamental to service design and delivery, and is beneficial for the young people involved as well as the organisation. This paper presents the findings of an evaluation of a youth participation model where tiered participation was attempted in a clinical youth mental health setting. To inform the ongoing development and improvement of a youth participation model, an evaluation was conducted consisting of three focus groups with the youth consultants, consultations with management about the implementation of the tiered participation model, and a review of records. The purpose of this evaluation was to identify possible barriers to implementation early on so these could be addressed and a youth participation model that meets the needs of all key stakeholders could be developed. The findings of this evaluation and the way in which these findings informed the model's development are discussed.